BORDER SURVEILLANCE AND CONTROL SYSTEM, PERSPECTIVES FOR ITS ESTABLISHMENT AND PRACTICAL APPLICATION - Vikainis, Roberts; Pokule, Inta (Border Security and Management, 2020)
Effective management of the European Union's external borders is a key priority and a condition for the proper implementation and maintenance of the Schengen area of free movement, which is one of the most important achievements of European integration. One of the cornerstones of effective management of the European Union's external borders is the timely, accurate and complete exchange of information between all the authorities responsible for controlling the European Union's external borders. The establishment of a European Border Surveillance System (EUROSUR) is an effective tool for such an exchange of information. Within the framework of the EUROSUR project implementation, Latvia has started work on the establishment of the Border Surveillance and Control System, which in the near future will become a basic tool in the development of the Latvian situation image with its further integration into the European situation image. The aim of the study is to study the EUROSUR implementation guidelines at the European Union level, to study the development and implementation of the Border Surveillance and Control System in the State Border Guard, to analyze its functionality and practical application possibilities, to study the existing problems in the Border Surveillance and Control System, and to evaluate.